THE FAMILY IN NURSING CARE FOR CHILDREN: AN INTEGRATIVE REVIEW - Aline Rigo Estevão; Fernanda Cassanho Teodoro; Magda Nanuck Ribas Pinto; Márcia Helena de Souza Freire; Verônica de Azevedo Mazza (Universidade Federal do Paraná, 2016)
This study aimed to investigate the scientific production on nursing care for children with a family focus. An integrative review was undertaken in five databases in June 2016. The inclusion criteria were: scientific publications disseminated between 2010 and 2015, in the form of a scientific article, in English, Portuguese and Spanish, and available through open access. The sample consisted of 16 articles, from which two thematic categories emerged: recognition of the family unit; limitations for childcare with a family focus. Childcare with a family focus values the relatives' participation in its execution, favors the professional-family bond with recognition of continuing care, and evidences the peculiarities of each family.